2022
DOI: 10.1186/s12967-022-03320-y
|View full text |Cite|
|
Sign up to set email alerts
|

Integrative analysis of metabolomics and proteomics reveals amino acid metabolism disorder in sepsis

Abstract: Background Sepsis is defined as a systemic inflammatory response to microbial infections with multiple organ dysfunction. This study analysed untargeted metabolomics combined with proteomics of serum from patients with sepsis to reveal the underlying pathological mechanisms involved in sepsis. Methods A total of 63 patients with sepsis and 43 normal controls were enrolled from a prospective multicentre cohort. The biological functions of the metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 44 publications
2
31
0
Order By: Relevance
“…The drop in intestinal bacterial diversity might have been partly responsible for the apparent scarcity of gut metabolites that we observed in sepsis patients. Consistent with previous findings based on serum specimens [ 5 ], metabolites involved in aromatic amino acid metabolism were the most interrupted. Our sepsis cohort exhibited reductions in a variety of aromatic amino acid metabolites, which are also closely linked with the gut microbiome and the outcome of sepsis, especially those involved in tryptophan and tyrosine metabolism.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The drop in intestinal bacterial diversity might have been partly responsible for the apparent scarcity of gut metabolites that we observed in sepsis patients. Consistent with previous findings based on serum specimens [ 5 ], metabolites involved in aromatic amino acid metabolism were the most interrupted. Our sepsis cohort exhibited reductions in a variety of aromatic amino acid metabolites, which are also closely linked with the gut microbiome and the outcome of sepsis, especially those involved in tryptophan and tyrosine metabolism.…”
Section: Discussionsupporting
confidence: 92%
“…Although previous studies have focused on the microbial features of patients with sepsis, the role of bacteria found to be altered in sepsis remains unclear. Metabolic signatures of sepsis have been determined in serum, but metabolic changes in the gut during sepsis are poorly understood [ 5 ]. The microbiota is known to generate metabolites that affect physiological processes of the host [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Untargeted metabolomics can reveal important biological associations in immunology research and identify novel metabolites/biomarkers specific to a disease (Ding et al , 2021b ; Alboniga et al , 2022 ; Aximujiang et al , 2022 ; Chen et al , 2022 ; Tian et al , 2022 ). For example, Zhu et al ( 2022 ) used high‐resolution untargeted metabolomics analysis to study influenza A virus subtype H1N1 (H1N1) infected patients and found an association between abnormal arginine metabolism produced by the virus and the immunity of the respiratory mucosa.…”
Section: Targeted and Untargeted Metabolomics For Immunology Researchmentioning
confidence: 99%
“…A novel technique, Raman spectroscopy, uses light scattering to non-destructively provide a structural fingerprint by which particles can be identified and has been used for identifying pathogens and metabolites, such as IL-6 [ 41 , 42 ]. In a cohort of 63 critically ill patients with sepsis and 43 controls, Chen et al used a combined proteomics and metabolomics approach to identify specific profiles in amino acid metabolism that could differentiate between patients with sepsis and healthy controls, with AUC values ranging from 0.81 to 0.96 [ 43 ]. In a validation group, the AUC value ranged from 0.62 to 1.00.…”
Section: Proteomics and Metabolomicsmentioning
confidence: 99%